FPSIR predicts clinical therapeutic responses and survival outcomes in patients with metastatic colorectal cancer undergoing first-line bevacizumab-containing chemotherapy - Li, Ya-Nan; Deng, Feng-Wen; Lan, Tian-Qi; Lu, Ying; Xiang, Lin; Song, Guo-Bin; Peng, Tian; Cheng, Xue-Xin; Ying, Hou-Qun (Frontiers in Immunology, 2026)
BackgroundIdentifying patients who are most likely to benefit from the combination of bevacizumab and chemotherapy (Bev/CT) is essential for the optimal management of metastatic colorectal cancer (mCRC). The aim of this study is to investigate the utility of chronic inflammatory biomarkers in predicting clinical response to Bev/CT and outcomes in patients with mCRC.Materials and methodsThis study enrolled 364 patients with mCRC undergoing first-line Bev/CT therapy. The patients were randomly assigned to discovery (n=249) and validation (n=115) cohorts, maintaining an approximate 2:1 ratio. Two machine learning algorithms, least absolute shrinkage and selection operator (LASSO)-penalized Cox regression and random survival forest (RSF), were employed to identify significant inflammatory biomarkers. Logistic regression, Kaplan-Meier survival analysis, and Cox regression analyses were conducted to evaluate the associations between the clinical outcomes and a product of fibrinogen-pre-albumin ratio and systematic inflammatory ratio (SIR) (FPSIR) and clinical outcomes. The primary endpoints included clinical disease control rate (DCR) and progression-free survival (PFS), 2-year overall survival (OS) was designated as a secondary endpoint.ResultsFollowing the integration of inflammatory biomarkers identified through the LASSO and RSF algorithms, FPSIR was independently associated with PFS in both the discovery (plog-rank<0.001, adjusted HR = 1.90, 95%CI=1.40-2.57) and validation cohorts (plog-rank=0.01, adjusted HR = 1.89, 95%CI=1.21-2.98). Furthermore, FPSIR-H was significantly associated with worse 2-year OS in the two cohorts (discovery cohort: plog-rank<0.001, adjusted HR = 2.15, 95%CI=1.49-3.10; validation cohort: plog-rank=0.02, adjusted HR = 1.93, 95%CI=1.06-3.51). Survival nomograms that incorporated CEA, CA19–9 and FPSIR (CCF) score, along with peritoneum metastases, number of metastatic sites, surgical intervention, and treatment regimens could effectively estimate 2-year PFS (AUC = 0.83) and 18-month OS (AUC = 0.71) in the discovery cohort, demonstrating robust performance in the validation cohort (AUC = 0.76 and 0.75 for PFS and OS, respectively). Elevated FPSIR was correlated with diminished DCR in Bev/CT therapy (p < 0.01, adjusted OR = 2.24, 95% CI = 1.27-3.96). Serial measurements of FPSIR exhibited dynamic changes that effectively monitored the efficacy of Bev/CT treatment.ConclusionPretreatment FPSIR was identified as a robust biomarker for predicting clinical efficacy and prognosis in mCRC patients receiving first-line Bev/CT, providing a promising strategy to address the long-standing challenge of treatment stratification.